Comparative glocal perspectives on European teacher education - Caena, Francesca (European journal of teacher education, 2014)
This article reports the findings of a PhD study, which offers comparative perspectives on teacher education in a period of reforms, inquiring into stakeholders' perceptions in English, French, Italian and Spanish contexts as case studies. The interaction of needs and constraints in European initial teacher education within higher education reforms, and the mediation between contrasting influences and diverse education cultures, are viewed as global phenomena: teacher education practices in different countries can be described as 'translations' of European policies, with innovative potential in glocal developments. This article explores some issues of the European dimension of teacher education, reporting the qualitative findings of the study, underpinned by a theoretical framework encompassing globalisation and social ecological studies. In the four case study contexts, the focus is on secondary teacher education; when a subject perspective is required, it concerns the area of modern languages, considering their transversal role in European education policies. Findings from the national case studies come from a limited empirical sample, but can be of interest in showing emerging tensions and trends.